- #1
caws
- 6
- 0
I am trying to prove by induction 1^3 + 2^3 + ... n^3 = [n(n+1)/2]^2
when n is a positive integer
Let P(n), if P(1) then n^3 = 1^3 = 1 and [n(n+1)/2]^2 = [1(1+1)/2]^2 = 1
the inductive hypothesis is 1^3 + 2^3 + ... k^3 = [k(k+1)/2]^2
Assuming P(k) is true then prove P(k+1) is true, insert (k+1) into problem
1^3 + 2^3 + ... k^3 + (k+1)^3 = [k+1(k+1+1)/2]^2 or [(k+1)(k+2)/2]^2
by the inductive hypothesis we get
[k(k+1)/2]^2 + (k+1)^3 = [(k+1)(k+2)/2]^2
am I thinking this through correctly? and where do I go from here?
when n is a positive integer
Let P(n), if P(1) then n^3 = 1^3 = 1 and [n(n+1)/2]^2 = [1(1+1)/2]^2 = 1
the inductive hypothesis is 1^3 + 2^3 + ... k^3 = [k(k+1)/2]^2
Assuming P(k) is true then prove P(k+1) is true, insert (k+1) into problem
1^3 + 2^3 + ... k^3 + (k+1)^3 = [k+1(k+1+1)/2]^2 or [(k+1)(k+2)/2]^2
by the inductive hypothesis we get
[k(k+1)/2]^2 + (k+1)^3 = [(k+1)(k+2)/2]^2
am I thinking this through correctly? and where do I go from here?
Last edited: